Formal methods in manufacturing - Campos Laclaustra, Javier, 1963-; Seatzu, Carla, 1971-; Xie, Xiaolan (CRC Press, 2014)
"Illustrated with real-life manufacturing examples, Formal Methods in Manufacturing provides state-of-the-art solutions to common problems in manufacturing systems. Assuming some knowledge of discrete event systems theory, the book first delivers a detailed introduction to the most important formalisms used for the modeling, analysis, and control of manufacturing systems (including Petri nets, automata, and max-plus algebra), explaining the advantages of each formal method. It then employs the different formalisms to solve specific problems taken from today's industrial world, such as modeling and simulation, supervisory control (including deadlock prevention) in a distributed and/or decentralized environment, performance evaluation (including scheduling and optimization), fault diagnosis and diagnosability analysis, and reconfiguration.Containing chapters written by leading experts in their respective fields, Formal Methods in Manufacturing helps researchers and application engineers handle fundamental principles and deal with typical quality goals in the design and operation of manufacturing systems"--Vydavatelská anotace
Keywords: výrobní systémy; automatizované výrobní systémy; řídicí systémy; teorie systémů; modelování a simulace; manufacturing systems; automated manufacturing systems; control systems; system theory; modeling and simulation; kolektivní monografie; collective monographs